(untitled) (Conferencea, 2023)
According to the conducted pedagogical observations, physical education lessons are held in the music room in many kindergartens. Such rooms are decorated with age-appropriate sports equipment in some kindergartens. But most kindergartens use small sports equipment (flags, bowling balls, cubes , hoops, sticks, etc.), but some kindergartens do not have them. Even if the kindergartens have basic sports fields, they are sufficient undecorated (health center, running tracks, jumping, throwing areas, etc.).